122k views
4 votes
Solve for x:
4(x + 2) = 3(x - 2)

2 Answers

5 votes

Answer: x= - 14

Explanation:

4(x + 2) = 3(x - 2)

4x+8 = 3x-6

-3x -3x

x+8 = -6

-8 = -8

x = -14

User Marteljn
by
5.1k points
5 votes

Answer:

x = -14

Explanation:

Step 1: Write equation

4(x + 2) = 3(x - 2)

Step 2: Solve for x

  1. Distribute: 4x + 8 = 3x - 6
  2. Subtract 3x on both sides: x + 8 = -6
  3. Subtract 8 on both sides: x = -14

Step 3: Check

Plug in x to verify it's a solution.

4(-14 + 2) = 3(-14 - 2)

4(-12) = 3(-16)

-48 = -48

User Pbogut
by
5.1k points